Platelet membrane-coated nanoparticles for targeted drug delivery and local chemo-photothermal therapy of orthotopic hepatocellular carcinoma. Issue 21 (6th May 2020) - Wu, Long; Xie, Wei; Zan, Hui-Ming; Liu, Zhongzhong; Wang, Ganggang; Wang, Yanfeng; Liu, Wei; Dong, Wenfei
Abstract : Specific targeted drug delivery and controllable release of drugs at tumor regions are two of the main challenges for hepatocellular carcinoma (HCC) therapy, particularly post metastasis. Abstract : Specific targeted drug delivery and controllable release of drugs at tumor regions are two of the main challenges for hepatocellular carcinoma (HCC) therapy, particularly post metastasis. Herein, we present a platelet membrane-facilitated local chemo-photothermal therapy strategy, in which polypyrrole (PPy) nanoparticles act as photothermal agents and along with antitumor drug doxorubicin (DOX) are encapsulated into platelet membranes (PLT-PPy–DOX). The particles are endowed with immune evasiveness and tumor targeting abilities from platelet membranes, and are then intravenously injected into an orthotopic mouse model of HCC. As expected, the PLT-PPy–DOX nanoplatforms were abundant in the tumor tissues. Hyperthermia was generated under laser irradiation (808 nm) not only to ablate tumor cells directly but also to increase the triggered release of DOX. This combination of local chemotherapy and photothermal therapy demonstrated excellent antitumor efficiency in suppressing primary tumor growth and inhibiting tumor metastases. This localized therapy which adopts biocompatible natural cell membranes and good biodegradable organic photothermal agents may provide new insights into designing biomimetic nano-vehicles for personalized therapy of HCC.